Exploring hospital waste recycling intention among hospital managers - Suriati, Deraman; Lee, Khai Loon; Muhamad Tamyez, Puteri Fadzline (Asian Scholars Network, 2023)
Recently, the healthcare industry has grown in importance as the number of hospitals has increased in response to the increased number of patients. This signified that the world faced more critical issues regarding hospital waste due to the environmental impact, and managers in the hospital needed to change the current hospital waste handling to reduce environmental pollution. In this study, the researcher used Theory of Planned Behavior comprehensively to reflect the manager's intention to recycle hospital waste. The purpose of this study is to investigate managers’ intention to recycle hospital waste in their organization. Others that, moderator effect on the managers intention to recycle hospital waste. Standardized structured questionnaires are distributed through email where the targeted respondent must be ranked manager position and above with medical background. A total of 181 usable were collected and data analyses by partial least square structural equation model (PLS-SEM). They revealed that managers’ intention is significantly influenced by the attitudes towards recycling intention and subjective norms has no significant towards managers recycling intention. However perceived behavioral control is not moderate between attitude/subjective norm and intention to recycle hospital waste. A total of 4 hypotheses were tested and one hypothesis were accepted, and three hypotheses rejected. The findings of this study provide important theoretical and practical implications for scholars, managers, and policymakers.